Kajian Kereta Api Komuter Surabaya - Sidoarjo (Susi) Sebagai Angkutan Umum Massal Di Surabaya - Arianto, Setio Boedi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Tir purpGfe of this stud!; is to make rm1mn; 115 mnss tmnsportntion tlmt nJ71m;s re needed l:n; tl7e Sumbcn.Jfland Sidoarjo residents. By using trend analysis n7etlwd and qual.itntirie descriptive analysis, it can amduded that tl7e pref£r!Ce of Susi Railwm; only m;Wle of amying 0.29% of tl7e total population Sidmrjoand Surabat;a, sud1 a little number or inadequate mass transportation fur a tm1m like Surabat;a andSidmrjo wit/1 a total population of 4,711,160 inhabitants. Susie trajecton; railwm; tracks alxJut 69% arestill single track and 31 % is double track Tizis rondition influence tl7e qunlity of EmTices to tl7e U£erS of railtransrxJrt, muse tl7ere are many patl?S tlmt Junie not lx:en double trnck milwm;, so tl7e journei; of Susie hasto m:zit for anotlv train to pass and then milway am rontinue the Susie joun1e1J Tizis rondition will affecttl7e trmiel Edrdule of Susie train. 771f nu nm of patl?S or routes Susi train is only 1 track, namely Sumbcn.Jfl- Porung via: z:ersa. T71f quantity nu of routes tlmt only one is nm; less if you lwie to Eenie tl7e nu of passengers wlw Jwie different purpGfes. But wl1fn vienied from tl7e plrysiad rondition of station infrastructureshelter is still in good rondition. Ow tJ7e last faie years (2005 - 2009) Susie has experienceddedining passengers muse tJ7e nwst of passengers wlw mn1f from Sidmrjo and Porvng f1£IZI(! mud.flow disaster, so many tl1e1; nwzie tl1fir residence. So the consequence, tJ1e11 switd1 to anotlv modelmiuse of tl7e Edzedule Susie train are mrely an time, nlso tlie lomtions tllnt senie tlJE milwm; station are notronnected or ezien less to ronnected witl1 feeder netnorks tlmt exist so tlmt users Susie commuter railtransportation often experienced difficulty in using Susie train to reach its final destination.